Минералогия (Mineralogy) 2020
DOI: 10.35597/2313-545x-2020-6-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromite-platinum mineralization of clinopyroxenite-dunite massif Zheltaya Sopka, North Ural

Abstract: The paper presents the new data on platinum group minerals (PGM) and chromite from the Zheltaya Sopka massif, North Urals. Few chromite bodies along with specifc composition of chromite indicate weak ore-forming processes developed in this massif. Minakawaite (RhSb) and chengdeite (Ir3Fe) are found for the frst time in the Uralian Platinum Belt. The PGM assemblage of the Zheltaya Sopka massif is compared with that of the Iov, Yuda, and Sosnovsky dunite massifs of the northern part of the Uralian Platinum Belt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Tomamaeite in Hokkaido is found only as minute particles in Pt-Fe(Cu) alloys (Fig. 7), and its occurrence is common in many localities (e.g., Orsoev et al, 2001;Grokhovskaya et al, 2005Grokhovskaya et al, , 2009Kozlov et al, 2011;Tolstykh et al, 2015;Grokhovskaya et al, 2019;Kuzmin et al, 2020). Based on these occurrences, tomamaeite is thought to occur by decomposition of Pt-Fe(Cu) alloys such as tulameenite, and its counterpart, the Pt-rich phase, should also occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomamaeite in Hokkaido is found only as minute particles in Pt-Fe(Cu) alloys (Fig. 7), and its occurrence is common in many localities (e.g., Orsoev et al, 2001;Grokhovskaya et al, 2005Grokhovskaya et al, , 2009Kozlov et al, 2011;Tolstykh et al, 2015;Grokhovskaya et al, 2019;Kuzmin et al, 2020). Based on these occurrences, tomamaeite is thought to occur by decomposition of Pt-Fe(Cu) alloys such as tulameenite, and its counterpart, the Pt-rich phase, should also occur.…”
Section: Discussionmentioning
confidence: 99%
“…Cu 3 Pt mineral was originally discovered in replacement rims composed of tulameenite on an isoferroplatinum core as a fine inclusion with diameters up to several tens of micrometers (Distler et al, 1986) and was subsequently reported to have similar occurrence in various localities (e.g., Orsoev et al, 2001;Grokhovskaya et al, 2005Grokhovskaya et al, , 2009Kozlov et al, 2011;Tolstykh et al, 2015;Grokhovskaya et al, 2019;Kuzmin et al, 2020). Grigor'eva et al (2018) reported the occurrence of 10 µm intergrowth grains consisting of orcelite, laurite, and Cu 3 Pt mineral in chromitite.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, grains of RhSbS composition were described by Tolstykh et al (2011) and Northern Urals by Kuzmin et al (2020) from the dunite of the Svetloborsky intrusion in the Urals Platinum Belt and from the clinopyroxenite-dunite Zheltaya Sopka massif.…”
Section: Introductionmentioning
confidence: 99%